2023
DOI: 10.3390/microorganisms11020407
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Oil by a Newly Isolated Strain Acinetobacter junii WCO-9 and Its Comparative Pan-Genome Analysis

Abstract: Waste oil pollution and the treatment of oily waste present a challenge, and the exploitation of microbial resources is a safe and efficient method to resolve these problems. Lipase-producing microorganisms can directly degrade waste oil and promote the degradation of oily waste and, therefore, have very significant research and application value. The isolation of efficient oil-degrading strains is of great practical significance in research into microbial remediation in oil-contaminated environments and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Thanks to our in-depth analysis, we were able to monitor changes in the gut microbiome at the level of microbial species. In particular, in our study, we identified several microbes that exhibited significant changes in abundance following the dietary intervention, including Acinetobacter junii, which, according to recent studies, is involved in the metabolism of fats [ 68 ]. The observed higher consumption of high-fat foods, including ice cream, Parmesan cheese, and oily fish, can thus explain the correlation with diet.…”
Section: Discussionmentioning
confidence: 92%
“…Thanks to our in-depth analysis, we were able to monitor changes in the gut microbiome at the level of microbial species. In particular, in our study, we identified several microbes that exhibited significant changes in abundance following the dietary intervention, including Acinetobacter junii, which, according to recent studies, is involved in the metabolism of fats [ 68 ]. The observed higher consumption of high-fat foods, including ice cream, Parmesan cheese, and oily fish, can thus explain the correlation with diet.…”
Section: Discussionmentioning
confidence: 92%
“…However, a consensus on the protein sequence identity threshold for pangenome analysis remains elusive. While many studies default to a 50% blastp threshold [ 64 67 ], our analyses (both BPGA and Roary) employed a stringent 95% blastp threshold [ 54 , 68 ], which ensures that only sequences with very high similarity are deemed homologous. Given the close evolutionary ties and subtle differences expected between NCTC 9931 and C24, a higher threshold may help in discerning highly conserved core genes from accessory and unique genes, minimizing false positives [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…53 C. acnes is also known to occur in human skin 54 and soil 55 , but as we do not see a historical pattern of DNA damage for this bacterium, it is more likely to be contemporary human contamination. Bacteria with less than 1000 reads but at least 0.1% abundance may be related to soil, rhizosphere ( A. junii , 56 C. gambrini , 57 K. rhizophila , 58 Methylosinus sp. C49, 59 M. luteus , 60 M. osloensis , 61 O. iheyensis , 62 P. merdae 63 ) or human intestinal tract, faeces ( Alistipes spp., 64,65 B. caccae , 66 D. succinatiphilus , 67 D. longicatena , 68 F. prausnitzii , 69 O. splanchnicus , 70 P. vulgatus 71 ).…”
Section: Discussionmentioning
confidence: 99%